Formal gender studies science communication in social sciences journals - Stundžė, Lijana (Information & Media, 2016)
Science and research are an integral part of the contemporary society – the participation of society in the development of science and technology and cooperation between science and business are an important factor in social changes. The wellbeing of contemporary society depends to a large extent on the continuous development of scientific knowledge, accumulation of technical and practical experience, a spirit of knowledge creation and entrepreneurship. Therefore, an effective science communication is important in order to ensure the generation of new knowledge and the application of research results in practice. The diffusion of knowledge and research results is implemented by means of science communication. Science communication ensures that society is informed about scientific innovations and therefore is an important tool for bringing together science and business, for encouraging innovations, and for informed decision-making. The aim of the article is to analyse the formal scientific communication in social sciences journals Sociologija. Mintis ir veiksmas, Filosofija. Sociologija, Socialiniai tyrimai, Socialinis darbas, Socialinių mokslų studijos, Tiltai, Acta paedagogica Vilnensia and to compare with previously carried out research of the journal Gender Studies and Research. Gender studies are a field of an interdisciplinary study devoted to issues of social injustice on the local and the global levels. It is a kind of science of civic engagement, which aims, among other things, to help to create a just social policy for both women and men. The aim of the present study is to analyse formal science communication in seven academic journals of social sciences. The study included the following dimensions of analysis: institutional affiliation of the authors of the articles, the language of the publications, topics of the publications, the gender of the authors; the leaders of scientific communication in this journal (the authors that have published the biggest number of articles) were identified, too. The study included 201 issues (all issues from 2004 to 2014) that contained 2614 articles published in the seven journals. The analysis revealed that the articles in the seven journals were published by researchers from 22 academic institutions of Lithuania and from abroad. This indicates the interdisciplinarity and international scope of the journals. The biggest proportion of the authors (19%) were from M. Romeris University, 14% from the Vilnius University, 13% from the Klaipėda University and Social Research Institute, 12% from the Vytautas Magnus University. Researchers not only from universities but also from research centres and institutes (Lithuanian Social Research Centre) take part in the formal science communication in these journals. Analysis also revealed that 15.5% of the articles were written in English (31% in the journal Gender studies and research). It should be noted that the participation of researchers from foreign academic institutions in the journal lacks consistency and continuity. Another dimension of the analysis was the distribution of the authors by gender: 16% of authors were male and 84% female. These data confirm the fact that female researchers are more involved into academic gender studies. The comparative analysis of the journals as an intermediary of formal science communication revealed several important aspects of scientific communication in these journals. The study has revealed that the most popular topics in the journals are similar. Analysis of the topics of the articles enables to identify most relevant areas of contemporary gender studies and research. The study of the publications of the journals identified the higher education and research institutions in Lithuania that conduct gender studies and disseminate their results. However, in respect of the internationalisation of the journals, the conclusion was made that publications in English and articles of authors from foreign academic institutions appear in the journals irregularly; there are issues that have no articles written by researchers from foreign institutions or articles by Lithuanian researchers written in English. The journals are an excellent channel for the dissemination of scientific information in gender studies. It is important, though, to aim for a regular and continuous scientific communication, to encourage publications by researchers from different disciplines, for a greater emphasis on the interdisciplinarity of gender studies and research, to expand the international scope of science communication, i.e., in summary, to strive for consistency and balance. This is important for achieving the effective scientific communication that helps to foster a wider dissemination of research results and improve the connection between the decision makers and knowledge, to inform society about social trends and enable it to strive for change, and to establish the principles of equal opportunities. It is worth noting that an effective dissemination of knowledge generated in gender studies is relevant not only for other researchers and professional community, but also could be very valuable in the processes of law and decision-making and could be used in initiatives for social, economic, and political changes. Moreover, in order to gain a comprehensive view on the whole scientific communication in gender studies, it is necessarily to expand the analysis beyond the formal communication scientist to scientist to other types of scientific communication (scientist to professional community, scientist to society), as well as to include other channels of formal communication.